'Tempos' management in primary care: a key factor for classifying adverse events, and improving quality and safety. - Amalberti, R; Brami, J (BMJ Quality & Safety, 2012)
BACKGROUND: The role of time management in safe and efficient medicine is important but poorly incorporated into the taxonomies of error in primary care. This paper addresses the lack of time management, presenting a framework integrating five time scales termed 'Tempos' requiring parallel processing by GPs: the disease's tempo (unexpected rapid evolutions, slow reaction to treatment); the office's tempo (day-to-day agenda and interruptions); the patient's tempo (time to express symptoms, compliance, emotion); the system's tempo (time for appointments, exams, and feedback); and the time to access to knowledge. The art of medicine is to control all of these tempos in parallel and simultaneously. METHOD: Two qualified physicians reviewed a sample of 1046 malpractice claims from one liability insurer to determine whether a medical injury had occurred and, if so, whether it was due to one or more tempo-related problems. 623 of these reports were analysed in greater detail to identify the prevalence and characteristics of claims and related time management errors. RESULTS: The percentages of contributing factors were as follows: disease tempo, 37.9%; office tempo, 13.2%; patient tempo, 13.8%; out-of-office coordination tempo, 22.6%; and GP's access to knowledge tempo, 33.2%. CONCLUSION: Although not conceptualised in most error taxonomies, the disease and patient tempos are cornerstones in risk management in primary care. Traditional taxonomies describe events from an analytical perspective of care at the system level and offer opportunities to improve organisation, process, and evidence-based medicine. The suggested classification describes events in terms of (unsafe) dynamic control of parallel constraints from the carer's perspective, namely the GP, and offers improvement on how to self manage and coordinate different contradictory tempos and day-to-day activities. Further work is needed to test the validity and usefulness of this approach.